Defining priorities for wildfire mitigation actions at the local scale: insights from a novel risk analysis method applied in Portugal - Benali, Akli; Aparício, Bruno A.; Gonçalves, Ana; Oliveira, Sandra (Frontiers in Forests and Global Change, 2023)
(THIS INFORMATION IS IN THE DOCUMENT)